Fabrication of Ti3C2Tx/In2O3 nanocomposites for enhanced ammonia sensing at room temperature. Issue 5 (1st March 2022) - Zhou, Ming; Han, Yutong; Yao, Yu; Xie, Lili; Zhao, Xueling; Wang, Jingrong; Zhu, Zhigang
Abstract: Ti3 C2 Tx, as a novel two-dimensional material, displays promising prospects in NH3 detection at room temperature. However, the NH3 detection limit of pristine Ti3 C2 Tx is still a major research concern. Therefore, it is important to explore new Ti3 C2 Tx -based nanocomposites for better NH3 -sensing performance. In the present experiment, Ti3 C2 Tx /In2 O3 nanocomposites were successfully synthesized by ultrasonication and characterized by XRD, FESEM, TEM, XPS, and BET. The optimal Ti3 C2 Tx /In2 O3 -based sensor had a high response of 63.8% (30.4 times higher than that of pristine Ti3 C2 Tx ) to 30 ppm NH3 at room temperature. In addition, the optimal Ti3 C2 Tx /In2 O3 -based sensor had stable repeatability, excellent selectivity, and long-term stability, while exhibiting excellent potential for NH3 detection at room temperature.